2000
DOI: 10.1038/eye.2000.77
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pupil dilation with tropicamide on vision and driving simulator performance

Abstract: The effect of pupil tested for statistical significance at the 95% level using one-tail paired t-tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…10 In a study of 28 patients, all of whom had fulfilled the UK visual requirements for driving before dilating drops, 22% failed to read a standard number plate at 20 m indoors post dilation and 14% of patients felt unsafe to drive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 In a study of 28 patients, all of whom had fulfilled the UK visual requirements for driving before dilating drops, 22% failed to read a standard number plate at 20 m indoors post dilation and 14% of patients felt unsafe to drive.…”
Section: Discussionmentioning
confidence: 99%
“…Mydriasis, however, increases screening time and can cause inconvenience to the patient especially those needing to drive and/or return to work. [10][11][12] We have assessed the detailed reasons, and predictors for an ungradeable nonmydriatic image. Predicting patients who fail nonmydriatic photography could help make screening more efficient by anticipating the need for mydriasis.…”
Section: Introductionmentioning
confidence: 99%
“…14 Pupillary dilation can also impair aspects of driving performance, and reduced contrast sensitivity is likely to be a contributing factor to this. 1,4 We believe patients should be warned that even if they satisfy the current legal requirements for driving after tropicamide administration, their vision can still be significantly impaired. The extent to which this affects their safety, and the safety of others, is still to be definitely answered and may vary between individuals.…”
Section: Resultsmentioning
confidence: 99%
“…1 However, others studies have shown only limited effects on high-contrast acuity and PelliRobson contrast threshold and no significant effects on low-contrast visual acuity and field of vision. [2][3][4] The aims of this study were to determine the effects of pupil dilatation on colour discrimination, and on contrast sensitivity over a wide range of spatial frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…Mydriasis using tropicamide 1% can interfere with the patient's lifestyle by reducing visual acuity and decreasing their amplitude of accommodation, restricting driving and the return to employment. [9][10][11][12] This may discourage attendance for the screening visit particularly in the younger age group who are more at risk for non-attendance. 13 A recent study found that many return to work and drive immediately after the appointment and the introduction of the routine use of drops may discourage attendance.…”
Section: Introductionmentioning
confidence: 99%